Indications for Zygomatic Implants: A Narrative Review (Academia Journal of Medicine, 2026)
Zygomatic implants represent a reliable graftless solution for the rehabilitation of patients with severe maxillary bone deficiency. Originally developed for maxillary defects following tumor resection, their clinical indications have expanded considerably with advances in surgical techniques and prosthetic protocols. This narrative review aims to summarize and critically discuss the contemporary indications for zygomatic implants based on evidence synthesized from recent systematic reviews and key clinical studies. Severe maxillary atrophy remains the most common indication, followed by avoidance of bone grafting procedures, management of failed grafts or implants, oncologic and traumatic defects, congenital anomalies, and medically compromised patients. Despite high reported survival rates, zygomatic implant therapy is technique sensitive and requires careful patient selection and surgical expertise. Standardization of indication criteria and high-quality prospective studies are needed to further refine clinical guidelines.
Keywords: Zygomatic implants, Maxillary atrophy, Implant dentistry